ANALISIS PERHITUNGAN OVERALL EQUIPMENT EFFECTIVENESS (OEE) PADA MESIN PACKING UNTUK MENINGKATKAN NILAI AVAILABILITY MESIN - Nursanti, Ida; Susanto, Yoko (Jurnal Ilmiah Teknik Industri, 2014)
PT. XYZ is a food and beverage company in Indonesia which produces many kinds of products with several different packing size since 1979. PT. XYZ always strives to improve production efficiency, especially in minimizing waste and loss that occur in every process of production. This study was conducted to calculate the Overall Equipment Effectiveness (OEE) of packaging machines at line 2 of PT. XYZ and identify the cause of the loss and waste that exist during production process. Overall Equipment Effectiveness (OEE) is a method to evaluate how effectively a manufacturing operation is utilized. The result of this research indicated that the OEE percentages of packaging machines both Weighing and SVB do not meet the company?s standards, which is 80 %. The main factor causing the declining value of OEE is machine availability and it is happened because the machine operator takes a long time to set up the machine.